AB0090 Reactivity To Citrullinated Peptide of 14-3-3eta Protein Is Associated with Worse Radiographic Outcomes in Patients with Recent-Onset Inflammatory Arthritis. (15th July 2016) - Carrier, N.; Marotta, A.; Maksymowych, W.P.; Boire, G.
Abstract : Background: 14–3-3η protein is citrullinated in the serum of Rheumatoid Arthritis (RA) patients. RA-associated HLA-DRB1 alleles preferentially bind citrullinated (cit) peptides but may bind both cit and arginylated (arg) peptides 1 . Autoreactivity to both cit and arg peptides may thus coexist in patients. Objectives: To examine serum reactivity to 8 peptides representing the arg and cit versions of 4 putative citrullination sites on the 14–3-3η protein and their association with RA serology and radiographic outcomes. Methods: Baseline serum reactivity to 4 pairs of cit and arg peptides was evaluated in a cohort of 331 patients (median age 60 years; 62% women) with recent onset polyarthritis (EPA). Receiver Operating Characteristic (ROC) curves were used to establish the optimal threshold of the ratios of reactivity to the 4 pairs of cit to arg peptides (Cit/Arg) for prediction of definite radiographic progression according to the Sharp/van der Heijde (SvH) score (ΔSvH ≥5) from baseline to 3 to 5 years. Spearman correlations were used to determine the relationships between the Cit/Arg ratios with anti-CCP2 and 14–3-3η. Generalized estimating equations (GEE) with repeated measures were used to predict risk of developing ΔSvH ≥5 over 5 years expressed as relative risk (RR) and 95% confidence intervals (95% CI). Results: At baseline, comparable reactivity was found against all 4 sets of cit peptides (2 linear: CIT4 and CIT7; 2 cyclic: CYC-CIT1 and CYC-CIT2) and their corresponding arg peptides (ARG4; ARG7; CYC-ARG1; CYC-ARG2). Linear peptides appeared better recognized in their arg form, and the reverse was true for the cyclic ones (Table ). Only the anti-CYC-CIT2/CYC-ARG2 ratio was significantly associated with ΔSvH ≥5 at 5 years (mean AUC=0.588, p=0.008); the best ROC cut-off for this ratio was 1.64. The anti-CYC-CIT2/CYC-ARG2 ratio was weakly correlated with anti-CCP2 (r=0.32, p<0.001) and with 14–3-3η (r=0.33, p<0.001), while anti-CCP2 and 14–3-3η protein were moderately correlated (r=0.53, p<0.001). Anti-CCP2 positivity, 14–3-3η ≥0.50 ng/ml, and anti-CYC-CIT2/CYC-ARG2 ≥1.64 were respectively present in 133 (40.2%), 119 (36%) and 80 (24.2%) patients and were associated with higher risk for ΔSvH ≥5 over time (RR 1.44 (1.14–1.80), p=0.002; 1.60 (1.28–2.00), p<0.001; RR 1.68 (1.35–2.09), p<0.001). Patients with both 14–3-3η ≥0.50 and anti-CYC-CIT2/CYC-ARG2 ≥1.64 had an increased risk for ΔSvH ≥5 compared to patients without either of the two (RR: 2.18 (1.68–2.83), p<0.001). The presence of only one marker also increased the risk (RR: 1.55 (1.20–2.01), p<0.001). In a multivariate GEE model with 14–3-3η ≥0.50, positive anti-CCP2, positive Rheumatoid Factor, positive anti-Sa/citrullinated vimentin, CRP >8.0 mg/L and anti-CYC-CIT2/CYC-ARG2 ≥1.64, only CRP and anti-CYC-CIT2/CYC-ARG2 were significant to predict ΔSvH ≥5 over 5 years (RR: 1.43 (1.11–1.84), p=0.006 and 1.45 (1.14–1.83), p=0.002; respectively). Conclusions: Many patients react against 14–3-3η arg peptides as well as against cit peptides. Citrullination at only one of 4 sites appeared linked to outcomes. An anti-CYC-CIT2/CYC-ARG2 ≥1.64 and elevated CRP protein both contributed independently to predict worse radiographic outcomes in patients with EPA. References: van Heemst J et al., Arthritis Rheum 2015;67(suppl 10) Disclosure of Interest: N. Carrier: None declared, A. Marotta Employee of: Augurex Life Sciences Corp. The 14–3-3η measurements were performed free of charge by Augurex, Augurex remaining totally blinded to clinical data. All the analyses were performed by investigators from Université de Sherbrooke and personnel of Centre hospitalier universitaire de Sherbrooke, without sharing of clinical and laboratory data of individual patients with Augurex personnel., W. Maksymowych Consultant for: Augurex Life Sciences Corp, co-inventor of the 14–3-3 biomarker platform, and has received honoraria from Quest Diagnostics for consulting services and royalty payments from the University of British Columbia., G. Boire Grant/research support from: The Sherbrooke EUPA cohort was supported by The Arthritis Society Grants 00/201 and RG06/108 and the Canadian Institutes for Health Research MOP-110959 (G Boire). AJF, PL, AMas and GB are part of the Centre de Recherche Clinique du Centre Hospitalier Universitaire de Sherbrooke, which received a team grant from the Fonds de la Recherche en Santé du Québec. Since 2007, the Sherbrooke EUPA cohort has also received financial support from the Canadian ArTritis CoHort (CATCH), a study designed and implemented by investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant. As of 2011, further support was provided by Hoffmann-La Roche Ltd, United Chemicals of Belgium (UCB) Canada Inc., Bristol-Myers Squibb Canada Co., Abbott Laboratories Ltd, and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson and Johnson Inc.)